Studi Empiris Kualitas Audit Pada Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Lampung - Muhammad Ichsan Siregar; Muhammad Hidayat; Abdullah Saggaf; Sri Maryati; Nilam Kesuma (Politeknik Ganesha Medan, 2022)
This study aims to obtain empirical evidence about the effect of competence, independence and objectivity on audit quality. The population in this study were all auditors who worked at the Supreme Audit Agency of the Republic of Indonesia. Researchers took a sample of 60 auditors who is still active. The data used in this study is primary data. The primary data used by the researcher is in the form of a questionnaire using a series of structured questions relating to the problem to be studied and related to the variables to be studied, namely: Competence, Independence, Objectivity and Audit Quality. Data collection techniques carried out in this study using a questionnaire technique. Researchers obtained data by sending a questionnaire via google form to the auditors of the Lampung Representative Audit Board. While the measuring instrument or research instrument used in this research is to use a Likert scale. Processing and analyzing data in this study using the SPSS program which is used to calculate statistical values in the form of descriptive statistical tests, data quality tests, multiple regression tests, classical assumption tests and hypothesis testing. Data analysis using multiple linear regression analysis is used to determine the direction and how much influence the independent variable has on the dependent variable. Based on the results of the study, it was found that competence and objectivity had a significant effect on audit quality, while independence had no significant effect on audit quality.